Nursing theory development - Sousa, Valmi; Hayman, Laura (Online Brazilian Journal of Nursing, 2002)
This paper analyzes knowledge and theory development in the discipline of nursing. Nursing theory development is characterized by nursing’s unique perspective: a distinct focus of the discipline of nursing. In a recognized nursing theory, the nursing metaparadigm’s concepts of person, environment, health, and nursing are defined, and the interrelationships among those concepts are described. Knowledge development in the discipline of nursing has generated and continues to generate philosophical, theoretical, and scientific knowledge, which serve as a basis for further reflections, investigations, and refinement, and as a source of new knowledge. In addition, nursing theory development has been related to borrowed or shared theories from or with other disciplines such as anthropology, education, sociology, and psychology.